2018
DOI: 10.1111/ina.12469
|View full text |Cite
|
Sign up to set email alerts
|

How home ventilation rates affect health: A literature review

Abstract: This paper reviews studies of the relationships between ventilation rates (VRs) in homes and occupant health, primarily respiratory health. Five cross-sectional studies, seven case-control studies, and eight intervention studies met inclusion criteria. Nearly all studies controlled for a range of potential confounders and most intervention studies included placebo conditions. Just over half of studies reported one or more statistically significant (SS) health benefits of increased VRs. Wheeze was most clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 34 publications
(193 reference statements)
0
25
0
1
Order By: Relevance
“…When the environmental performance of building envelopes is analysed, ventilation is identified as one of the main variables affecting energy demand, the degree of environmental comfort (ISO 7730: 2005; UNE-CR 1752: 2008) [1,2], the accumulation rate of CO 2 , suspended particles and pollutants (EN 15251: 2007) [3], and respiratory health in prolonged periods of exposure [4].…”
Section: Introductionmentioning
confidence: 99%
“…When the environmental performance of building envelopes is analysed, ventilation is identified as one of the main variables affecting energy demand, the degree of environmental comfort (ISO 7730: 2005; UNE-CR 1752: 2008) [1,2], the accumulation rate of CO 2 , suspended particles and pollutants (EN 15251: 2007) [3], and respiratory health in prolonged periods of exposure [4].…”
Section: Introductionmentioning
confidence: 99%
“…8,9,11,12 Several related studies of classroom ventilation have shown that lower air change rates in classrooms were significantly associated with lower learning performance. 1,2,5,6 Many studies also have found that poor ventilation in the early residence was significantly associated with increased childhood asthma, wheeze, and rhinitis, 3,[36][37][38][39] which could decrease abilities in learning among the sick children. These findings are consistent with our explanation for the significant association of birth quarter of the year with learning capacity in childhood because of poor 1st and 4th quarters household ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Whether household ventilation and indoor-outdoor temperature variation are associated with learning capacity in childhood and adolescence is a hot topic of interest in the "indoor air quality (IAQ)" field. [1][2][3][4][5][6] Some toxicological studies have hypothesized that long-term exposure to high carbon dioxide (CO 2 ) or carbon monoxide (CO) concentrations due to insufficient ventilation may restrict brain development during gestation and infancy and lead to learning disabilities in childhood and adolescence. [7][8][9][10][11][12] However, it is very difficult to onsite inspect long-term ventilation and estimate its association with early learning capacity in a large sample size.…”
Section: Introductionmentioning
confidence: 99%
“…This context generates a situation of specificity where further study is necessary, given the different exposure scenarios with a greater influx from the outside although varying over time.Given that ventilation is one of the main variables which affects the degree of environmental comfort [23,24], the European ventilation standard EN 13779:2008 [25], through its Spanish transposition [26], establishes a minimum outdoor airflow to guarantee the adequate indoor air quality (IAQ) in non-residential buildings. Mainly, its focus is to control CO 2 concentration, pollutants, and suspended particles [27] to avoid the development of symptomatology and respiratory health related to prolonged periods of exposure [28]. According to the national regulation, this ventilation must be mechanically controlled since 2007, also including an air filtering system, to ensure this IAQ, but given that the adaptation could entail a huge investment and a higher energy consumption, several public institutions in Spain are imposing natural ventilation as the only system for IAQ control, against standards.In this way, previous studies in classrooms of southern Spain [16,17], Portugal [12], France [29], Italy [30], and other south European locations [31] have shown poor indoor conditions, both thermal and clean air, which can relate to the appearance of symptoms like dizziness, dry skin, headache, or tiredness.…”
mentioning
confidence: 99%
“…Given that ventilation is one of the main variables which affects the degree of environmental comfort [23,24], the European ventilation standard EN 13779:2008 [25], through its Spanish transposition [26], establishes a minimum outdoor airflow to guarantee the adequate indoor air quality (IAQ) in non-residential buildings. Mainly, its focus is to control CO 2 concentration, pollutants, and suspended particles [27] to avoid the development of symptomatology and respiratory health related to prolonged periods of exposure [28]. According to the national regulation, this ventilation must be mechanically controlled since 2007, also including an air filtering system, to ensure this IAQ, but given that the adaptation could entail a huge investment and a higher energy consumption, several public institutions in Spain are imposing natural ventilation as the only system for IAQ control, against standards.…”
mentioning
confidence: 99%